2014
DOI: 10.3389/fcimb.2014.00155
|View full text |Cite
|
Sign up to set email alerts
|

Fatal cerebral malaria: a venous efflux problem

Abstract: Most Plasmodium falciparum-infected children with cerebral malaria (CM) die from respiratory arrest, but the underlying pathology is unclear. Here we present a model in which the ultimate cause of death from CM is severe intracranial hypertension. Dynamic imaging of mice infected with P. berghei ANKA, an accepted model for experimental CM, revealed that leukocyte adhesion impairs the venous blood flow by reducing the functional lumen of postcapillary venules (PCV). The resulting increase in intracranial pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 79 publications
(113 reference statements)
2
20
0
Order By: Relevance
“…Interestingly, HIV coinfection shifted the distribution of activated IBA1 + CD68 + monocytes/macrophages away from the luminal surface in CM + Seq hi patients ( Figure 6, E-H) -a pattern also observed with CD3 + CD8 + T cells ( Figure 5). Collectively, these data demonstrate that high iRBC sequestration is associated with a strong innate cerebrovascular immune response due to iRBC and immune cell sequestration within venous vasculature in which flow velocities are already significantly decreased compared with arterial vasculature (39). We therefore examined whether there were differences in CD3 + CD8 + T cell accumulation in arteries versus veins.…”
mentioning
confidence: 99%
“…Interestingly, HIV coinfection shifted the distribution of activated IBA1 + CD68 + monocytes/macrophages away from the luminal surface in CM + Seq hi patients ( Figure 6, E-H) -a pattern also observed with CD3 + CD8 + T cells ( Figure 5). Collectively, these data demonstrate that high iRBC sequestration is associated with a strong innate cerebrovascular immune response due to iRBC and immune cell sequestration within venous vasculature in which flow velocities are already significantly decreased compared with arterial vasculature (39). We therefore examined whether there were differences in CD3 + CD8 + T cell accumulation in arteries versus veins.…”
mentioning
confidence: 99%
“…Cerebral malaria was a malaria complication characterized by decreased awareness or the appearance of neurological disorders (ataxia, seizures, paraplegic, etc.). The emergence of various neurological disorders and decreased awareness of cerebral malaria is associated with the occurrence of excessive inflammatory processes in response to a high degree of parasitemia [4].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of CM is still poorly clarified. However, several studies demonstrated the presence and the role of raised intracranial pressure (ICP) in the occurrence of deaths and neurological sequelae [3] [4] [5] [6] [7]. The reference method for the diagnosis (gold standard) of raised ICP is continuous measurement of ICP with intraventricular catheter or intraparenchymal sensor.…”
Section: Introductionmentioning
confidence: 99%